Convergence results based on graph-Reich contraction in fuzzy metric spaces with application - Shamoona Jabeen; Mehmet Emir Koksal; Mudasir Younis (Nonlinear Analysis)
This article introduces a novel class of Reich-type contractions that meet the graph preservation criteria in the context of complete fuzzy metric spaces. The provided contraction condition is satisfied through various forms of contractive mappings via directed graphs in the literature. Our key result is the natural extension of fuzzy metric spaces to fuzzy metrics enriched with a graph, which adds the understanding of fixed points in metric spaces within the realm of graph structure. The findings are further supported by examples and applications.